2021
DOI: 10.3390/cancers13215368
|View full text |Cite
|
Sign up to set email alerts
|

Breast Invasive Ductal Carcinoma Classification on Whole Slide Images with Weakly-Supervised and Transfer Learning

Abstract: Invasive ductal carcinoma (IDC) is the most common form of breast cancer. For the non-operative diagnosis of breast carcinoma, core needle biopsy has been widely used in recent years for the evaluation of histopathological features, as it can provide a definitive diagnosis between IDC and benign lesion (e.g., fibroadenoma), and it is cost effective. Due to its widespread use, it could potentially benefit from the use of AI-based tools to aid pathologists in their pathological diagnosis workflows. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Figure 1 shows an overview of the training method. The training methodology that we used in the present study was the same as reported in our previous studies Kanavati and Tsuneki (2021a); Tsuneki and Kanavati (2021); Tsuneki et al (2022). For completeness we repeat the methodology here.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows an overview of the training method. The training methodology that we used in the present study was the same as reported in our previous studies Kanavati and Tsuneki (2021a); Tsuneki and Kanavati (2021); Tsuneki et al (2022). For completeness we repeat the methodology here.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…In the field of computational pathology as a computer-aided detection (CADe) or computer-aided diagnosis (CADx), deep learning models have been widely applied in histopathological cancer classification on whole-slide images (WSIs), cancer cell detection and segmentation, and the stratification of patient clinical outcomes Yu et al (2016); Hou et al (2016); Madabhushi and Lee (2016); Litjens et al (2016); Kraus et al (2016); Korbar et al (2017); Luo et al (2017); Coudray et al (2018); Wei et al (2019); Gertych et al (2019); Bejnordi et al (2017); Saltz et al (2018); Campanella et al (2019); Iizuka et al (2020). Previous studies have looked into applying deep learning models for ADC classification in stomach Iizuka et al (2020); Kanavati and Tsuneki (2021b); Kanavati et al (2021a), colon Iizuka et al (2020); Tsuneki and Kanavati (2021), lung Kanavati and Tsuneki (2021b); Kanavati et al (2021b), breast Kanavati and Tsuneki (2021a); Kanavati et al (2022), and prostate Tsuneki et al (2022) histopathological specimen WSIs. As for the gastric poorly differentiated ADC classification on WSIs, we have developed deep learning models based on endoscopic biopsy specimens Kanavati and Tsuneki (2021b); Kanavati et al (2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is a shortage of experienced pathologists, who require years of training and examination, which creates challenges for cancer centers [ 5 ]. In the automatic analysis of WSIs, glass slides are digitized to produce on-screen WSIs, and artificial intelligence, in particular deep learning technology, is applied [ 6 , 7 , 8 ]. The emergence of digital WSIs has made it possible to introduce deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Das et al [ 28 ] adopted a multi-instance network to exclude input disturbance and acquire cancer features. Kanavati et al [ 7 ]. used the EfficientNet-B1 to detect breast invasive ductal carcinoma, with loose annotation.…”
Section: Introductionmentioning
confidence: 99%
“…The process, however, involves manual feature engineering by expert pathologists who must carefully observe and examine the glass slide of biopsy specimens. Capturing these specimens into images makes them available for use in computer-aided detection/diagnosis [ 14 ]. Approaches such as machine learning (ML) and, more specifically, deep learning (DL), have been explored in recent years due to their successes in aiding in the prognosis and diagnosis of other medical conditions [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%